NILAI MORAL PADA FILM NANTI KITA CERITA TENTANG HARI INI KARYA ANGGA DWIMAS SASONGKO - Eka Septyawanti, Farah; Elmustian, Elmustian; Rumadi, Hadi (Jurnal Ilmu Budaya, 2021)
This study aims to describe the moral values ​​contained in the film Nanti Kita Cerita Tentang Hari Ini. This type of research is qualitative research, using descriptive analysis research methods. Data analysis is inductive or qualitative, and the results of the study emphasize meaning rather than generalization. In the film Nanti Kita Stories About Today by Angga Dwimas Sasongko, there is a form of moral values ​​film, namely individual moral values, which include: honesty, courage, patience, hard work, self-sacrifice, humility., take responsibility, lie. And social moral values include cooperation, help, love, deliberation. The researcher found that the results of the data were 60 the number of moral values ​​contained in the dialogue between characters, which were divided into social moral values ​​consisting of honesty 6, courage 6, patience 6, hard work 4, willingness to sacrifice 2, humility 1, responsibility 8, lying 2 Social moral values ​​consist of: cooperation 2, like to help 2, love 19, deliberation 2. Where the moral value of love is the most found data and humility is the least data found.